PENGENALAN KEWIRAUSAHAAN DIGITAL DIMASA PANDEMI MELALUI KEGIATAN FOTOGRAFI - Tri Nugroho Budi Santoso (Jurnal Kewirausahaan dan Bisnis, 2021)
The pandemic period is a major factor in various changes that occur in various fields of life, one of which is affected by the economy and education. Digital entrepreneurship is a new discourse in overcoming economic problems in Indonesia. The purpose of this research is to collaborate with photography competition activities to introduce digital entrepreneurship during the pandemic. This study uses a mixed research approach, namely a combination of qualitative and quantitative research methods. Qualitatively by using descriptive qualitative research to describe or describe a phenomenon of introducing digital entrepreneurship during a pandemic through photography activities. The quantitative method uses descriptive statistical analysis to calculate the respondent's data as measured by the Linkert scale. Based on the results of the analysis, it is known that digital entrepreneurship can be recognized by various simple technologies, various photography techniques can indirectly introduce entrepreneurship activities digitally more deeply as well as provide motivation in pioneering entrepreneurial activities. Based on respondent data, obtained from instruments with a Likert scale, it is known that a score of 91 out of a maximum score of 100 lies in the area close to Strongly Agree. The conclusions that can be drawn from the photography competition activities carried out can provide insight into digital entrepreneurship.Keywords: Digital Entrepreneurship, Photography Competition, Pandemic Period